Improving Quality Of The Understanding Of Pancasila Values And Achievement IN History Learning Through Cooperative Learning Model Picture And Picture Method at SMAN 4 Kupang - Margison A. Blegur (Universitas Sebelas Maret, 2020)
This research aims to improve the understanding of Pancasila values and improve the achievement of learning history in the midst of the identity of the nation. Strengthening historical learning determines how implementation will impact the quality of the nation's identity, by improving the quality of historical learning by planting Pancasila values will impact students in general. The number of negative influences on a country is a fading of sublime values that can be seen in a country, and this is what is happening in Indonesia today, with the influence of globalization one of which is the influence of outside cultures that do not conform to Pancasila values. Through the application of cooperative learning models with picture and picture methods, this research uses class action research methods through two cycles consisting of the introduction, core activities, and cover. The results showed that the cooperative learning method with picture and picture model can improve the understanding of Pancasila values of 3rd graders in SMA N 4 KUPANG. Furthermore, the results of this study are expected to improve the material understanding of Pancasila values continuously in SMA N 4 Kupang NTT.